Smaller countries' way to competitiveness : Central America in a new world economic order during the 90s - Zepeda Bermudez, Gerardo ([s.n.] [S.l.], 1992)
Looks at Central America today and the aftermath of import substitution strategies. Focuses on the role played by small and medium-sized enterprises in Central American industrialization. Outlines the Central American Economic Action Plan (PAECA). Notes special regional programs to support small and medium enterprises.